Chilling injury of tomato fruit was alleviated under low-temperature storage by silencing Sly-miR171e with short tandem target mimic technology - Zhao, Keyan; Chen, Rulong; Duan, Wenhui; Meng, Lanhuan; Song, Hongmiao; Wang, Qing; Li, Jiangkuo; Xu, Xiangbin (Frontiers in Nutrition, 2022)
In this study, the role of Sly-miR171e on post-harvest cold tolerance of tomato fruit was researched. The results showed that overexpression of Sly-miR171e (miR171e-OE) promoted postharvest chilling injury (CI) of tomato fruit at the mature red (MR) and mature green (MG) stage. Contrasted with the wild type (WT) and miR171e-OE fruit, the knockdown of Sly-miR171e (miR171e-STTM) showed a lower CI index, lower hydrogen peroxide (H2O2) content, and higher fruit firmness after harvest. In the fruit of miR171e-STTM, the expression level of GRAS24, CBF1, GA2ox1, and COR, and the GA3 content were ascended, while the expression levels of GA20ox1 and GA3ox1 were descended. The research demonstrated that CI in tomato fruit was alleviated at low temperature storage by silencing Sly-miR171e with short tandem target mimic (STTM) technology. Furthermore, it also provided helpful information for genetic modification of miR171e and control of CI in the postharvest fruit.